A History of Population Health - Mackenbach, Johan P. (Clio Medica, 2020)
In A history of Population Health Johan P. Mackenbach offers a comparative study of trends in 40 specific diseases in Europe and their explanation, focusing on the causes of the spectacular improvements in people’s health since the early 18th century. ; Readership: Health care professionals with an interest in medical history, students and scientists in public health, economics, sociology, and related disciplines, and anyone interested in the history of health and disease.